'Nothing about us, without us': Voices of leaders of disabled people's organisation in management of disability fund. Issue 1 (2021) - Opoku, Maxwell Peprah; Nketsia, William
Abstract: In 2005, the Ghanaian government established cash grants for persons with disabilities (PWDs). However, PWDs are still living under deplorable conditions, which have raised questions about the involvement of fellow PWDs in the disbursement of cash grants. Using a human rights-based approach, nine participants with disabilities (hearing, visual and physical) who were leaders of the Disabled People's Organisation in four districts were interviewed to explore their perspectives, which was thematically analysed. The results showed that leaders were not consulted or involved in the allocation of grants to PWDs. This paper discusses the need for bureaucrats to respect and involve PWDs in matters concerning their livelihoods.